An Integrated BAC and Genome Sequence Physical Map of Phytophthora sojae - Xuemin Zhang; Chantel Scheuring; Sucheta Tripathy; Zhanyou Xu; Chengcang Wu; Angela Ko; S. Ken Tian; Felipe Arredondo; Mi-Kyung Lee; Felipe A. Santos; Rays H. Y. Jiang; Hong-Bin Zhang; et al. (Molecular Plant-Microbe Interactions, 2006)
Phytophthora spp. are serious pathogens that threaten numerous cultivated crops, trees, and natural vegetation worldwide. The soybean pathogen P. sojae has been developed as a model oomycete. Here, we report a bacterial artificial chromosome (BAC)-based, integrated physical map of the P. sojae genome. We constructed two BAC libraries, digested 8,681 BACs with seven restriction enzymes, end labeled the digested fragments with four dyes, and analyzed them with capillary electrophoresis. Fifteen data sets were constructed from the fingerprints, using individual dyes and all possible combinations, and were evaluated for contig assembly. In all, 257 contigs were assembled from the XhoI data set, collectively spanning approximately 132 Mb in physical length. The BAC contigs were integrated with the draft genome sequence of P. sojae by end sequencing a total of 1,440 BACs that formed a minimal tiling path. This enabled the 257 contigs of the BAC map to be merged with 207 sequence scaffolds to form an integrated map consisting of 79 superscaffolds. The map represents the first genome-wide physical map of a Phytophthora sp. and provides a valuable resource for genomics and molecular biology research in P. sojae and other Phytophthora spp. In one illustration of this value, we have placed the 350 members of a superfamily of putative pathogenicity effector genes onto the map, revealing extensive clustering of these genes.